410 Phase I study of intratumoral NBTXR3 in combination with anti-PD-1 in patients with advanced cancers. (9th November 2020) - Shen, Colette; Frakes, Jessica; Niu, Jiaxin; Weiss, Jared; Caudell, Jimmy; Jameson, Katherine; Said, Patricia; Seiwert, Tanguy
Abstract : Background: Cancer immunotherapies have shown promising clinical outcomes; however, the majority of patients are non-responders or will develop resistance during the course of treatment. One of the current challenges is to increase the response rate to immune checkpoint inhibitors (ICIs). Combining immunotherapy with radiation therapy (RT) is emerging as a valuable strategy to prime the immune response. However, RT dose and ultimate efficacy are limited by toxicity related to exposure of healthy tissues. First-in-class radioenhancer NBTXR3, administered by one-time direct intratumoral injection, is designed at the nanoscale to increase RT dose deposit with subsequent increase in tumor cell killing, without increasing toxicity to normal tissue. Preclinical and early clinical data suggest NBTXR3/RT can prime the immune system and act as an in situ vaccine leading to an anti-tumor immune response, producing both local and systemic (abscopal) effects. We hypothesize NBTXR3/RT in combination with anti-PD-1 (NBTXR3/RT/PD-1), will act synergistically to increase the proportion of ICI responders or convert ICI non-responders to responders. Methods: A multicenter, open-label, phase I trial [NCT03589339 ] evaluating safety and tolerability of NBTXR3/RT/PD-1 in three cohorts: (1; H&N) Locoregional recurrent or recurrent and metastatic head and neck squamous cell carcinoma (HNSCC) amenable to re-irradiation of the HN field, (2; lung) lung or (3; liver) liver metastases from any primary cancer eligible for approved anti-PD-1 treatment. NBTXR3 injected volume is based on a percentage of baseline tumor volume. Stereotactic body RT (SBRT) is delivered as per standard practice. The primary objective is to determine NBTXR3/RT/PD-1 recommended phase II dose in each cohort. Secondary objectives are to evaluate anti-tumor response (objective response rate), safety and feasibility of NBTXR3 injection, and NBTXR3 body kinetic profile. Results: To date 6 patients have been treated: 3 in H&N (2 anti-PD-1 naïve) and 3 in lung (all anti-PD-1 non-responders. No DLT or SAE has been observed. Grade 2 nausea related to NBTXR3 or injection procedure was observed in H&N. 2 H&N patients and 3 lung patients have completed RT and initiated anti-PD-1 treatment. RT-related safety profile was as expected. Tumor shrinkage was observed in 1 anti-PD-1 naive and 2 anti-PD-1 non-responders and additional preliminary efficacy and updated safety results will be presented. Conclusions: To date, NBTXR3 administration activated by SBRT in combination with anti-PD-1 treatment has been safe and well tolerated in patients with advanced cancers. Promising early signs of efficacy in anti-PD-1 naïve, as well as in patients having progressed on previous anti-PD-1 therapy will be presented. Trial Registration: NCT03589339 Ethics Approval: This study was approved by local institution's review board